Examining the Effects of Financial Literacy, Family Financial Socialization, Parental Education, and Parental Income on Financial Behavior among University Students Living Away from Home - Umi Rachmah Damayanti; Ade Ria Nirmala; Ratna Nuraini; M. Sabri; Siti Intan Nurdiana Wong Abdullah (Research in Accounting Journal (RAJ), 2026)
University students living away from home are required to manage their finances independently while facing various economic and social challenges. This study aims to examine the influence of financial literacy, family financial socialization, parental education, and parental income on the financial behavior of university students living away from home. A quantitative approach was employed using primary data collected through questionnaires. The sample consisted of 375 university students living away from home from the Faculty of Economics and Social Sciences, selected using the accidental sampling technique. Data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that financial literacy, family financial socialization, parental education, and parental income have a positive and significant effect on financial behavior. The coefficient of determination (R²) of 67.5% shows that variations in financial behavior can be explained by these four variables, while the remaining 32.5% is influenced by other factors outside the research model. The findings suggest that the financial behavior of university students living away from home is influenced not only by financial knowledge but also by family financial socialization and parents’ socioeconomic background.